Analisa Fatwa Dewan Syariah Nasional No. 07/DSN-MUI/IV/2000 Tentang Jaminan dalam Pembiayaan Mudharabah - Piryanti, Meri (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2024)
Background. The National Sharia Council (DSN-MUI) Fatwa No. 07/DSN-MUI/IV/2000 on Mudharabah Financing regulates provisions regarding the use of collateral in mudharabah contracts. This issue is significant because, in principle, sharia emphasizes trust between the shahibul maal (capital provider) and the mudharib (entrepreneur), while collateral is viewed as a means of risk mitigation. Aim. This study aims to analyze the content of the fatwa, particularly the position of collateral in mudharabah financing, and to assess its relevance and implications for the practice of Islamic financial institutions in Indonesia. Methods. The research applies a library research method with a normative-juridical and qualitative approach, examining the text of the fatwa, literature on fiqh muamalah, Islamic banking regulations, as well as practical applications in financial institutions. Results. The analysis shows that the DSN-MUI Fatwa allows the use of collateral in mudharabah financing not to cover business losses, but rather as a safeguard in cases of negligence or misuse of funds by the mudharib. This provision aligns with the prudential principle in Islamic finance. However, in practice, the use of collateral sometimes shifts the meaning of mudharabah from a trust-based partnership toward a more transactional nature. Therefore, a balance is required between sharia compliance and the practical needs of financial institutions to ensure that the essence of justice and partnership in mudharabah contracts is preserved.